2015
DOI: 10.1101/019471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cf-4 receptor-like protein associates with the BAK1 receptor-like kinase to initiate receptor endocytosis and plant immunity

Abstract: Summary 35• The first layer of plant immunity is activated by cell surface receptor-like kinases (RLKs) 36 and proteins (RLPs) that detect infectious pathogens. Constitutive interaction with the 37 RLK SUPPRESSOR OF BIR1 (SOBIR1) contributes to RLP stability and kinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…The role of BRs in B. napus defence against Lm becomes more significant in the light of recent studies revealing the involvement of BRs in PAMPtriggered immunity (PTI) (Albrecht et al, 2012), and the striking overlap that exists between the PAMP recognition complexes and the plant receptor complexes for the recognition of intercellular filamentous pathogens (Liebrand et al, 2014). Several recent studies have shown that SOBIR1 and BAK1 (BRI1-associated kinase 1) form a complex with tomato RLPs to recognize C. fulvum, the pathogen of tomato (Postma et al, 2015). Lm shares a high degree of similarity with C. fulvum, in term of its infection process and host plant receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…The role of BRs in B. napus defence against Lm becomes more significant in the light of recent studies revealing the involvement of BRs in PAMPtriggered immunity (PTI) (Albrecht et al, 2012), and the striking overlap that exists between the PAMP recognition complexes and the plant receptor complexes for the recognition of intercellular filamentous pathogens (Liebrand et al, 2014). Several recent studies have shown that SOBIR1 and BAK1 (BRI1-associated kinase 1) form a complex with tomato RLPs to recognize C. fulvum, the pathogen of tomato (Postma et al, 2015). Lm shares a high degree of similarity with C. fulvum, in term of its infection process and host plant receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that overlap exists between the PRR perception of PAMPs and the RLP recognition of effectors secreted by the apoplastic fungi. A recent report by Postma et al (2015) showed that upon induction by Avr4, Cf4, interacts with BAK1. The recently discovered transmembrane LRR-RLK, SUPPRESSOR OF BIR1-1 (SOBIR1), is also required for ETI initiated by RLPs ( Liebrand et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the G-domain in the proteins only contained a short cytoplasmic tail, a typical RLKs are required by tomato Cf-4 and Cf-9 against C. fulvum (Liebrand et al, 2013(Liebrand et al, , 2014Postma et al, 2015). In addition, SOBIR1 is essential for tobacco and tomato LeEix2 and tomato Ve1 proteins to induce plant defence against the fungus expressing the xylanase or V.…”
Section: C-terminal Flanking Regionsmentioning
confidence: 86%
“…SOBIR1 requires the GxxxG dimerization motif in its transmembrane domain to form constitutive complexes with RLPs (Bi et al, 2016). For instance, the LRR-RLP Cf and I proteins of Solanum lycopersicum require association with the signalling partner SOBIR1 and/or BAK1 to confer resistance against the fungal pathogens C. fulvum and F. oxysporum, respectively (Catanzariti et al, 2017;Liebrand et al, 2014;Postma et al, 2015). These two partners are also part of the B. napus Rlm2 and…”
Section: Extracellular Lrr Classmentioning
confidence: 99%
See 1 more Smart Citation